THE REFLECTION OF AMERICAN VALUES IN MOST SUBSCRIBED SELF-HOSTED AMERICAN YOUTUBERS’ VIDEOS = Giá trị văn hoá mỹ phản ánh qua video tự sản xuất của Youtuber Mỹ được nhiều người theo dõi nhất - Nguyễn, Hải Anh (2020)
Based on the theoretical background of cross-cultural communication, this study aims at investigating the American values reflected in the most subscribed self-hosted American YouTube videos. The chosen research method is Qualitative content analysis. The main instruments of data collection are observation. The process of data selection goes through three stage: Selection of video categories, of YouTube channels, and of channels‘ videos. Three most viewed videos from four most subscribed hosted American YouTuber in ―People & Vlogs‖ were transcribed and analysed. Evidence from each videos were then coded and regrouped into each group of American values. The study reviews that all American values listed in the foundation theory were shown through these mentioned videos. The analysis also brings about a new perspectives over the relations between each groups of value within American society, in which individualism acts as the core value.